Peningkatan Pelayanan Jasa dengan Menggunakan Metode Servqual dan Metode Quality Function Deployment (Studi Kasus di Larissa Skin Care and Hair Treatment, Surakarta) - Roni Zakaria R; Fakhrina Fahma; Sugesti Sri Linuwih (Performa: Media Ilmiah Teknik Industri, 2007)
Larissa Skin Care & Hair Treatment is one of service industry serving treatment of skin and hair which have the concept of ”Back to Nature”. by the using number of the same service industry in Surakarta and the awareness of costumers toward how important the quality is beauty clinique in Surakarta have to stunggle order to be able to give service in accordance with costumers needs and desines. To solve these challenges, research was done to observe ang to know what is exactly desires and needs of costumers in beauty clinique Larissa Surakarta. It used Servqual method is used to calculate the discrepancy between costumers preception and their hope. Quality Function Deployment is used as mean to evaluate quality of service given to costumers by arranging programs though house of quality. By combining those two methods of Quality Function Deployment method and Servqual method, hopefully it would improve performance better. The research resulted 3 variables which have positive gap so it could be said thet it had fulfilled the level of costumers desire. While the variables that couldn’t the fulfilled yet were focused on variables which have negative gap. Based on the house of quality, 5 variables werw choosed in priority scale to improve the quality of service, they are houlding towards costumers given by kapters, beautician, and doctors. beauty equipment used, recovery or the result of using Larissa treatment, how Larissa solve the probles or complains from costumers, and friendliness of staffs and doctors toward costumers.